(untitled) (Sains Humanika, 2019)
Divorce not only affects the husband and wife, but can also interfere with the psychological development of the child and to some extent disrupting their academic performance. Despite this, not all children whose parents are divorced face academic difficulties. This study aims to explore the emotional states of high-achieving students whose parents are divorced, and how they dealt with these emotions. This qualitative study utilised semi-structured interviews conducted to five randomly selected respondents who were high-achieving students whose parents were divorced. Data were analysed using the narrative analysis approach. The results showed that majority of the respondents experience negative emotions such as sadness, anger, depressed and sense of loss. Nonetheless, they also experience positive emotions namely surrender, acceptance and gratitude. They are able to manage their emotions because of their strengths and the accessibility of support from parents and others. In conclusion, high-achieving students with divorced parents are capable of managing their emotions and achieve academic excellence with the support of parents and other people around them.